Identification of mitochondria-related genes in calcific aortic valve disease by integrated analysis of single-cell and bulk transcriptomic atlases - Ziling Mai; Huijun Du; Yuhan Chen; Yaner Lu; Bingchen Liu; Deqiang Sun (Journal of Physiology and Biochemistry, 2026)

Hierarchical nanofluidic membrane with improved anti-fouling performance toward osmotic energy harvesting - Yang Chen; Kexin Sun; Jie Liu; Yankang Du; Ziling Wang; Xiao Zhang; Yulei Li; Yanglei Xu; Feng Xu (Chemical Engineering Journal, 2026)

Bioinspired HP-β-CD/TA co-assembled coating enhances acid tolerance and fermentation performance of Lactiplantibacillus plantarum XJ25 - Jiajun Huang; Mengxin Han; Ruotong Pang; Xinle Wang; Yangnan Yan; Xuan Wang; Ziling Yang; Shuwen Liu; Xianghong Xie (Food Research International, 2026)

Cysteine-engineered MXene interlayers enable highly efficient electro- and photothermal de-icing - Haobo Mao; Qingyu Chen; Xiaoyan Ruan; Ziling Pang; Xiangying Meng; Yiqi Liu; Hanyi Huang; Kejia Chen; Jiayin Liu; Yu Yu; Songmei Wu; Lixin Yang (Chemical Engineering Journal, 2026)

Dynamic optimization of retained-ditch height for turning-stage planning in inclined coal seam open-pit mines - Yu Wen; Ziling Song; Shiyang Xia; Wenfang Liu (Arabian Journal of Geosciences, 2026)

A large-scale comparative evaluation of DNA metabarcoding primers for profiling freshwater eukaryotic microalgal biodiversity - Yuan Luo; Ziling Yan; Si-Yu Zhang; Kai Liu; Meng Yao (Journal of Environmental Management, 2026)

A small heat shock protein from Arabidopsis thaliana regulates glyceraldehyde-3-phosphate dehydrogenase in the drought tolerance - Jieru Chen; Hongting Liu; Zichun Ma; Xinyi Yu; Huiyue Ji; Sipei Huang; Xinyue Zhu; Ziling Liu; Yangyang Chen; Hai Liao; Jiayu Zhou (Plant Cell Reports, 2026)

Dietary Lysophospholipids Enhance the Function of Lutein Rather than Lycopene in Pacific White Shrimp - Chaojie Zhu; Ziling Song; Zhengwei Ye; Yanjiao Zhang; Jiahao Liu; Lindong Xiao; Chenchen Bian; Qiang Ma; Yuliang Wei; Mengqing Liang; Houguo Xu (Fishes, 2026)
Our previous studies found that lipid emulsifiers can promote the absorption and deposition of liposoluble pigments in shrimp. The present study aimed to further investigate the effects of liposoluble pigments lutein (LUT) and lycopene (LYC), and their combination with lysophospholipids (LPL), on the growth performance, body coloration, and lipid composition of Pacific white shrimp Penaeusvannamei. Five diets were formulated: a control diet (Control), Control + 0.02% lutein (LUT), Control + 0.02% lycopene (LYC), LUT + 0.1% LPL (LUT + LPL), and LYC + 0.1% LPL (LYC + LPL). The feeding trial lasted for 8 weeks. There were no significant differences in shrimp growth and body composition among all groups. Both LUT and LYC increased the redness (a*) and yellowness (b*) of cooked shrimp. LPL synergistically enhanced the pigmentation-improving effects of LUT but weakened those of LYC. Additionally, LYC decreased the redness and yellowness of raw shrimp. Both LUT and LYC reduced the contents of saturated fatty acids and EPA while increasing the DHA content; LPL further enhanced this modulatory effect. In conclusion, LPL acts synergistically with LUT to improve the body coloration and modify the fatty acid composition of Pacific white shrimp, but its effect with LYC is limited.

The Application of Machine Learning in the Development of Co-Amorphous Dry Powder Inhalation - Ziling Zhou; Xian Chen; Yuxin Liu; Rongjiao Zheng; Junxiang Huang; Xin Pan; Chuanbin Wu; Junhuang Jiang (AAPS PharmSciTech, 2026)

Metabolic engineering of Halomonas cupida for co-mineralization of phenol and p-nitrophenol in high-saline wastewater - Ziling Yuan; Yujie Liu; Haomin Chen; Jing Dang; Xinyu Zhang; Xinyao Li; Ruihua Liu; Chao Yang (Journal of Environmental Management, 2026)

Metabolic engineering of Pseudomonas putida for mineralization of 1,2-dichloroethane and 2,4-dichlorophenoxyacetic acid and its application in wastewater bioremediation - Xinyu Zhang; Yujie Liu; Ziling Yuan; Haomin Chen; Danyang Ma; Bingzhi Li; Ruihua Liu; Chao Yang (Journal of Environmental Chemical Engineering, 2026)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

An electrochemical immunobiosensor based on PVA/PDA/PEDOT conductive antifouling coating for direct detection of CNS injury biomarker in forensic clinical sample - Ziling Guo; Sibo Wang; Leihan Wang; Jing Wang; Menghan Li; Yumei Li; Sumin Liu; Dan Liu; Chenghong Gu; Haiping Wu; Xiaolin Yu; Ying Zhu (Analytica Chimica Acta, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Correction: Flavisericum labens gen. nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the seawater of Dongshan Bay - Jieyi Li; Ziling Xu; Zhiyi Su; Guohua Liu; Yue Xu; Dan Lin; Kai Tang (Antonie van Leeuwenhoek, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

A single fluorescent probe for simultaneous detection of polarity, viscosity, and esterase - Zehua Han; Taihe Han; Ziling Tang; Qin Huang; Junbao Ma; Shuai Mu; Huayu Wang; Xiaoyan Liu; Haixia Zhang (Analytica Chimica Acta, 2025)

A R2R3-MYB transcription factor LmMYB111 positively regulates chlorogenic acid and luteoloside biosynthesis in Lonicera macranthoides - Yanni Liu; Juan Lou; Guohua Liu; Qingqing Li; Zhengyan Cao; Peiyin Wu; Haoyang Mashu; Zhilin Liu; Jia Deng; Ziling Yang; Jiang Guo; Ning Tang; et al. (Plant Science, 2025)

Flavisericum labens gen. nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the seawater of Dongshan Bay - Jieyi Li; Ziling Xu; Zhiyi Su; Guohua Liu; Yue Xu; Dan Lin; Kai Tang (Antonie van Leeuwenhoek, 2025)

TcJAMYC5 positively regulates paclitaxel biosynthesis in Taxus chinensis var. Mairei - Shiyu Cai; Lina Xue; Ziling Tao; Fengxiu Li; Qiao Liu; Wen Wan; Jihong Jiang; Ludan Li; Xiaoying Cao (Plant Molecular Biology, 2025)

Creating a multifunctional degrader for co-mineralization of p-nitrophenol and 1,2-dichloroethane and its application in wastewater bioremediation - Yujie Liu; Yuting Jiang; Yan Meng; Weini Xiong; Ziling Yuan; Ruihua Liu; Chao Yang (Journal of Hazardous Materials, 2025)

A self-sustainable DNA amplification circuit for sensitive microRNA imaging - Chuanyi Liu; Ziling Huang; Zhigang Li; Xiaojiao Dai; Qingmin Chen; Min Chen; Yi Xu; Xiaomei Chen; Fuan Wang; Quansheng Chen; Jie Wei (Analytica Chimica Acta, 2025)

Cloning and functional characterization of sesquiterpene synthase genes from Inonotus obliquus using a Saccharomyces cerevisiae expression system - Qiao Liu; Junzhi Peng; Ziling Tao; Jiluan Zhang; Weifan Wu; Zhiwu Tan; Tao Zhou; Xiaoying Cao; Jihong Jiang (World Journal of Microbiology and Biotechnology, 2025)

In-situ redox processes of electrosorption-based systems during As, Cr detoxification and recovery: mechanisms, applications and challenges - Haoyu Yin; Liu Huang; Yunbo Dai; Ziling Zheng; Yuquan Li; Bo Tang; Xu Wang; Le Shi (Chemical Engineering Journal, 2025)

Starch/polyacrylamide hydrogels with flexibility, conductivity and sensitivity enhanced by two imidazolium-based ionic liquids for wearable electronics: Effect of anion structure - Ziling Zhang; Lu Lu; Bingbing Hong; Qichao Ye; Li Guo; Chao Yuan; Bo Liu; Bo Cui (Carbohydrate Polymers, 2025)

Multiple DNA cycle amplification for highly efficient detection of mercury pollution in food - Ziling Huang; Chuanyi Liu; Zhigang Li; Qingmin Chen; Dong Li; Xiaomei Chen; Quansheng Chen; Jie Wei (Food Chemistry, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Novel seamless shell-core microbead for probiotics encapsulation: Influence of gel structure on storage stability and gastrointestinal activity - Hongxia Gao; Youfa Xie; Ziling Li; Chunqing Bai; Liqiang Zou; Wei Liu (Food Hydrocolloids, 2024)

Roles of THEM4 in the Akt pathway: a double-edged sword - Wen Xie; Weidong Liu; Lei Wang; Bin Zhu; Cong Zhao; Ziling Liao; Yihan Li; Xingjun Jiang; Jie Liu; Caiping Ren (Journal of Zhejiang University-SCIENCE B, 2024)

Degradation of trichloroacetic acid by Fe/Ni bimetallic reactive PMS with hierarchical layered structure - Guangda Mu; Yuxiang Yang; Ziling Chang; Hongming Yuan; Yan Huang; Irum Batool; Xiangnong Liu; Chaoying Ni (Environmental Research, 2024)

Imbalance of T follicular helper cell subsets trigger the differentiation of pathogenic B cells in idiopathic membranous nephropathy - Bishun Deng; Huijie Huang; Li Deng; Ziling Zhao; Miao Liu; Haibiao Lin; Xiaowan Wang; Ruimin Tian; Xiaoxin Tu; Anping Peng; Enyu Liang; Kun Bao; et al. (Inflammation Research, 2024)

Pyrite-assisted degradation of methoxychlor by laccase immobilized on Fe3S4/earthworm-like mesoporous SiO2 - Jiaqi Yang; Yuxiang Yang; Ziling Chang; Yan Huang; Hongming Yuan; Yi Zhao; Xiangnong Liu; Chaoying Ni (Environmental Science and Pollution Research, 2024)

Identification of Immune Infiltration and Iron Metabolism–Related Subgroups in Autism Spectrum Disorder - Wenyan Huang; Zhenni Liu; Ziling Li; Si Meng; Yuhang Huang; Min Gao; Ning Zhong; Sujuan Zeng; Lijing Wang; Wanghong Zhao (Journal of Molecular Neuroscience, 2024)

Phosphotungstic acid supported on Zr-SBA-15 as an efficient catalyst for one-pot conversion of furfural to γ-valerolactone - Zonghui Liu; Zhongze Zhang; Yali Zhou; Ziling Wang; Mingyang Du; Zhe Wen; Bing Yan; Qingxiang Ma; Na Liu; Bing Xue (Fuel, 2024)

Corrigendum to ‘The combination of S-doped ZIF-8 with graphene oxide for enhanced near-infrared light photocatalytic and photothermal sterilization’ [Chem. Eng. J. 455 (2023) 140857] - Ziling Zhou; Huiping Zhu; Xiangmei Liu; Yuelin Lv; Yufeng Zheng; Dafu Chen; Shengli Zhu; Zhaoyang Li; Zhenduo Cui; Shuilin Wu (Chemical Engineering Journal, 2024)

Fe0Ni0 bimetal co-immobilized horseradish peroxidase on ZIF-8@HMON for degradation of trichloroacetic acid - Yuxiang Yang; Xiaocui Huang; Mengyang Dong; Ziling Chang; Hongming Yuan; Yan Huang; Xiangnong Liu; Jianbo Zhang; Anbang Dai (Chemical Engineering Journal, 2024)

BCNO quantum dots-based ratiometric fluorescence platform integrated with portable device: Hypoxanthine sensing for on-site assessment of meat freshness with deep learning - Xinyi Liu; Ziling Li; Ziyu Wang; Xipeng Cui; Wenhao Li; Manman Wang; Yu He (Chemical Engineering Journal, 2024)

Corrigendum to “The combination of S-doped ZIF-8 with graphene oxide for enhanced near-infrared light photocatalytic and photothermal sterilization” [Chem. Eng. J. 455 (2023) 140857] - Ziling Zhou; Huiping Zhu; Xiangmei Liu; Yuelin Lv; Yufeng Zheng; Dafu Chen; Shengli Zhu; Zhaoyang Li; Zhenduo Cui; Shuilin Wu (Chemical Engineering Journal, 2024)

Antimicrobial Peptides Targeting Streptococcus mutans: Current Research on Design, Screening and Efficacy - Xinxin Ying; Guanglu Xue; Pengxiang Sun; Ziling Gan; Ziqian Fan; Bo Liu; Yaoting Han; Jiaqian Yang; Jing Zhang; Aiping Lu (Current Microbiology, 2024)

Evapotranspiration partitioning based on underlying conductance in a complex tree-grass orchard ecosystem in the humid area of southern China - Ningbo Cui; Shunsheng Zheng; Shouzheng Jiang; Mingjun Wang; Lu Zhao; Ziling He; Yu Feng; Yaosheng Wang; Daozhi Gong; Chunwei Liu; Rangjian Qiu (Agricultural and Forest Meteorology, 2024)

High-Zn wheat alleviates P-Zn antagonism by improving Zn activation, acquisition, and translocation at key growth stages - Jun Yang; Junfeng Xu; Ziling Wang; Xuemei Zhang; Zikang Guo; Li Wang; Chenrui Liu; Qing Sun; Chao Li; Yinglong Chen; Mei Shi; Zhaohui Wang (Field Crops Research, 2023)

Systematic and dynamic impacts of the COVID-19 pandemic on marine economic development, air pollution and energy consumption: A case study of China's coastal regions - Chenggang Li; Yuanrui Zhang; Ziling Chen; Xue Wang; Mu Yue; Jiaqi Liu; Yuchun Jiang; Zhen Zhao; Guoli Cai (Ocean & Coastal Management, 2023)

Construction of a self-sufficient DNA circuit for amplified detection of kanamycin - Yumeng Li; Qingyang Si; Chuanyi Liu; Ziling Huang; Qingmin Chen; Tianhui Jiao; Xiaomei Chen; Quansheng Chen; Jie Wei (Food Chemistry, 2023)

Substantial dimerized G-quadruplex signal units engineered by cutting-mediated exponential rolling circle amplification for ultrasensitive and label-free detection of exosomes - Ziling Ding; Yunyun Wei; Xiaopeng Liu; Fei Han; Zhangrun Xu (Analytica Chimica Acta, 2023)

Development of human health criteria in China for benzo[a]pyrene: A comparison of deterministic and probabilistic approaches - Ziling Yu; Mingdeng Xiang; Ruixue Ma; Chuan Yi; Guocheng Hu; Xichao Chen; Yupei Liu; Yunjiang Yu (Chemosphere, 2023)

Construction of a simple dual-mode ATP-sensing system for reliable fish freshness evaluation - Qingyang Si; Yumeng Li; Ziling Huang; Chuanyi Liu; Xiaomei Chen; Jie Wei; Fuan Wang (Analytica Chimica Acta, 2023)

Annual Dynamics of Bird Community at a Coastal Wetland and Their Relation to Habitat Types: The Example of Beidagang Wetland, Northern China - Mengxuan He; Ziling Dai; Xunqiang Mo; Zhengwang Zhang; Jin Liu; Weipan Lei; Weiqing Meng; Beibei Hu; Wenbin Xu (Journal of Marine Science and Engineering, 2023)
In order to provide more scientific guidance for wetland bird protection, this study addressed the dynamics of the bird community sorted by ecotypes, classifications and threat categories from 2015 to 2019, and non-metric multidimensional scaling analysis, generalized additive models and the Mantel test were used to examine the relationships between bird communities and habitat types. The results showed that: (1) The abundance of birds peaked in 2017 at 88,258 individuals and then declined. Moreover, there was an inverse trend between species richness and abundance of birds, meaning greater abundance is associated with fewer species. (2) Swimming birds were dominant ecotypes and Anseriformes possessed the highest abundance. It was noteworthy that the abundance of critically endangered birds (Aythya baeri and Grus leucogeranus) and the species richness of endangered birds increased. (3) Building land and farmland had dominant impacts on the composition of bird community. Wading birds and birds in Gruiformes were significantly impacted by building land and farmland, and near threatened species were substantially influenced by farmland. Therefore, maintaining good connectivity between protected areas and surrounding areas is one of the best ways to effectively manage biodiversity of the target area. This research may provide a broader insight for coastal wetland bird habitat management and bird diversity preservation.

The combination of S-doped ZIF-8 with graphene oxide for enhanced near-infrared light photocatalytic and photothermal sterilization - Ziling Zhou; Huiping Zhu; Shuilin Wu; Yuelin Lv; Yufeng Zheng; Dafu Chen; Shengli Zhu; Zhaoyang Li; Zhenduo Cui; Xiangmei Liu (Chemical Engineering Journal, 2023)

Effect of Different Colored LED Lighting on the Growth and Pigment Content of Isochrysis zhanjiangensis under Laboratory Conditions - Bu Lv; Ziling Liu; Yu Chen; Shuaiqin Lan; Jing Mao; Zhifeng Gu; Aimin Wang; Feng Yu; Xing Zheng; Hebert Ely Vasquez (Journal of Marine Science and Engineering, 2022)
Light is one of the most important environmental factors affecting the growth and reproduction of algae. In this study, the effect of various LED colors on the productivity, chlorophyll (Chl-a, Chl-b, and total Chl), protein, and carbohydrate content of Isochrysis zhanjiangensis in indoor culture was investigated. Microalgae monocultures were cultivated under five different colors (red, green, blue, yellow, and white) for twenty-one days. The microalgae cultured under red light exhibited a higher specific growth rate (0.4431 ± 0.0055 µ day−1), and under white light a higher productivity (0.0728 ± 0.0013 g L−1 day−1). The poorest performance was observed under yellow and green lights. Interestingly, green light exhibited the highest levels of chlorophylls (Chl-a, 1.473 ± 0.037 mg L−1; Chl-b, 1.504 ± 0.001 mg L−1; total Chl, 2.827 ± 0.083 mg L−1). The highest protein content was observed under the white light (524.1935 ± 6.5846 mg L−1), whereas the carbohydrate content was remarkably high under the blue light (24.4697 ± 0.0206 mg L−1). This study is important in terms of the selection of light at the appropriate color (wavelength) to increase the content of organic compounds desired to be obtained indoors with the potential for commercially produced cultures.

Development and characterization of 23 microsatellite markers for the endangered beetle Carabus lafossei (Coleoptera, Carabidae) - Shengli Jing; Xiaoyan Huang; Mingyang Liu; Kun Zhang; Liming Wang; Zhe Yang; Ziling Liao; Niyan Xiang; Xinjing Zheng; Bin Huang (Conservation Genetics Resources, 2017)

Dibenzo-α-pyrones from the endophytic fungus Alternaria sp. Samif01: isolation, structure elucidation, and their antibacterial and antioxidant activities - Jin Tian; Linyun Fu; Zihao Zhang; Xuejiao Dong; Dan Xu; Ziling Mao; Yang Liu; Daowan Lai; Ligang Zhou (Natural Product Research, 2017)

Overexpression of Hiwi Inhibits the Cell Growth of Chronic Myeloid Leukemia K562 Cells and Enhances Their Chemosensitivity to Daunomycin - Yalin Wang; Yan Jiang; Cuicui Bian; Yi Dong; Chao Ma; Xiaolin Hu; Ziling Liu (Cell Biochemistry and Biophysics, 2015)

Overexpression of Hiwi Inhibits the Growth and Migration of Chronic Myeloid Leukemia Cells - Yalin Wang; Yan Jiang; Ning Ma; Bailu Sang; Xiaolin Hu; Xiaofeng Cong; Ziling Liu (Cell Biochemistry and Biophysics, 2015)

Separation and purification of bioactive botrallin and TMC-264 by a combination of HSCCC and semi-preparative HPLC from endophytic fungus Hyalodendriella sp. Ponipodef12 - Ziling Mao; Ruiya Luo; Haiyu Luo; Jin Tian; Hongwei Liu; Yang Yue; Mingan Wang; Youliang Peng; Ligang Zhou (World Journal of Microbiology and Biotechnology, 2014)

KRC transcripts: identification of an unusual alternative splicing event - Chi-Ho Mak; Ziling Li; Carl Eugene Allen; Yiling Liu; L.-C. Wu (Immunogenetics, 1998)